Akibat Hukum Dari Pembatalan Perjanjian Kerjasama - Abdul Rokhim; Dewi Fatmawati (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2024)
Agreement is a legal relationship between two or more parties based on an agreement to give rise to legal consequences of rights and obligations for both parties. Cancellation of the agreement can only be done if it is known that there was an oversight, fraud, or coercion from one of the parties when making the agreement. Oversight, fraud, or coercion are reasons that can cancel the agreement. This study aims to analyze the legal consequences of the cancellation of the cooperation agreement according to the Civil Code (KUH Perdata) and the legal remedies that can be taken by the parties as a result of the cancellation of the cooperation agreement. This type of research is normative legal research using a statutory approach. The results of the study show that the legal consequence of canceling the cooperation agreement is returning to its original position as it was before the agreement occurred. Meanwhile, the legal remedy resulting from the cancellation of the cooperation agreement is actively asking for the cancellation of the agreement which does not fulfill its subjective requirements in court or passively waiting for the opposing party to submit an annulment in court.